Americanah : a novel - Adichie, Chimamanda Ngozi (2013)
"A young woman from Nigeria leaves behind her home and her first love to start a new life in America, only to find her dreams are not all she expected"--
Keywords: Immigrants -- Fiction; Refugees -- Fiction; Nigerians -- Fiction; Nigerians -- Fiction; FICTION / Literary; FICTION / African American / General; FICTION / Cultural Heritage